One Nanoscale Zn(II)-Nd(III) Complex With Schiff Base Ligand: NIR Luminescent Sensing of Anions and Nitro Explosives - Liu, Xia; Yang, Xiaoping; Ma, Yanan; Liu, Jieni; Shi, Dongliang; Niu, Mengyu; Schipper, Desmond (Frontiers in Chemistry, 2020)
One Zn-Nd complex [Zn2Nd4L2(OAc)10(OH)2(CH3OH)2] (1) was synthesized from Schiff base ligand bis(3-methoxysalicylidene)ethylene-1,2-phenylenediamine (H2L). 1 shows nanoscale rectangular structure with sizes of about 0.8 × 1.1 × 2.8 nm. Excited by ligand-centered absorption bands, 1 shows typical NIR emission of Nd3+ ion. Interestingly, 1 exhibits lanthanide luminescent response towards anions and nitro explosives, especially to H2PO2- and TNP at ppm level.